Your answer is going to be fifteen plus r
Answer:
Distribute, then combine like terms, subtract 10 from both sides of the equation, simplify, divide both sides of the equation by the same term, and simplify to get your solution.
Step-by-step explanation:
1.) Distribute
6−2(4−5)=40
6−8+10=40
2.) Combine like terms
6a-8a+10=40
-2a+10=40
3.) Subtract 10 from both sides of the equation
-2a+10=40
-2a+10-10=40-10
4.) Simplify
subtract the numbers
-2a+10-10=40-10
-2a=40-10
subtract the numbers
-2a=40-10
-2a=30
-2a=30
5.) Divide both sides of the equation by the same term
-2a=30
![\frac{-2a}{-2} =\frac{30}{-2}](https://tex.z-dn.net/?f=%5Cfrac%7B-2a%7D%7B-2%7D%20%3D%5Cfrac%7B30%7D%7B-2%7D)
6.) Simplify
cancel terms that are in both the numerator or denominator
![\frac{-2a}{-2} =\frac{30}{-2}](https://tex.z-dn.net/?f=%5Cfrac%7B-2a%7D%7B-2%7D%20%3D%5Cfrac%7B30%7D%7B-2%7D)
a=![\frac{30}{-2}](https://tex.z-dn.net/?f=%5Cfrac%7B30%7D%7B-2%7D)
Divide the numbers
a=![\frac{30}{-2}](https://tex.z-dn.net/?f=%5Cfrac%7B30%7D%7B-2%7D)
a=-15
a=-15
7.) Solution
a=-15
Answer:
42 gallons 45% antifreeze
28 gallons 95% antifreeze
Step-by-step explanation:
If x is volume of 45% antifreeze, and y is volume of 95% antifreeze, then the total volume is:
x + y = 70
And the total amount of antifreeze is:
0.45 x + 0.95 y = 0.65 (70)
Solving by substitution:
0.45 x + 0.95 (70 − x) = 0.65 (70)
0.45 x + 66.5 − 0.95 x = 45.5
21 = 0.5 x
x = 42
y = 28
Answer:
I am confusion
Step-by-step explanation:
Hello! And thank you for your question!
First we are going to expand the equation:
<span>−2<span>m^<span><span>2</span><span></span></span></span>−2mn+8m−10m+10n+nm+4<span>n<span><span>^2</span><span></span></span></span>−5n
Then we are going to combine like terms:
</span><span><span>−2<span>m<span><span>^2</span><span></span></span></span>+(−2mn+mn)+(8m−10m)+(10n−5n)+4<span>n<span><span>^2</span><span></span></span></span></span>
</span>
Then finally, simplify:
−2<span>m<span><span>^2</span><span></span></span></span>−mn−2m+5n+4<span>n<span>^<span>2
Final Answer:
</span></span></span>
−2m^2−mn−2m+5n+4n^2